BLOCKCHAIN TECHNOLOGY IMPLEMENTATION ON MEDICAL RECORDS DATA MANAGEMENT: A REVIEW OF RECENT STUDIES - Dian Budi Santoso; Anis Fuad; Guntur Budi Herwanto; Ahmad Watsiq Maula (Jurnal Riset Kesehatan, 2020)
Blockchain first introduced and implemented in digital currency management and transactions. Its application to medical records data management is a novelty. This paper described the implementation of blockchain technology in the healthcare industry, especially in medical records data management A literature review was conducted on three popular databases, ScienceDirect, SpringerLink, and IEEE Xplore with the keywords "health", "medical record" and "blockchain" with "research article" and "conference proceeding" filters. There are a few articles that meet the criteria to review indicated that the implementation of blockchain technology in medical records data management is a novelty and still in the early phase. Blockchain is a potential technology in supporting the implementation of electronic medical records, especially related to data integration and privacy. Several scientific publications related to the implementation of blockchain for medical records data management shown that the implementation of this technology will make the patient have full control over their health data. Yet there are still many challenges in the implementation both from the user side and the technology infrastructure.